Inflammatory complications of shunt operations - Yu. A. Orlov; I. P. Tkachik; A. V. Shaversky; N. V. Plavsky; L. L. Marushchenko (Ukrainian Neurosurgical Journal, 2007)
The inflammatory complications of shunt operations in 1990–1999 and 2005 years were analyzed. The frequency of the inflammatory complications was 5,2 and 5,1%. Some changes in infections’ etiology and their pharmacoresistance were established. In 2005 the amount of hydrocephaly cases, combined with congenital CNS disorders and cases of gram-positive microorganisms have increased. Also pharmacoresistance to the traditional antibiotics increased. The risk factors of inflammatory complications development after shunt operations were established.